H(2)O(2) treatment or serum deprivation induces autophagy and apoptosis in naked mole-rat skin fibroblasts by inhibiting the PI3K/Akt signaling pathway - Zhao, Shanmin (Oncotarget, 2016)
Naked mole-rats (NMR; Heterocephalus glaber) display extreme longevity and resistance to cancer. Here, we examined whether autophagy contributes to the longevity of NMRs by assessing the effects of the PI3K/Akt pathway inhibitor LY294002 and the autophagy inhibitor chloroquine (CQ) on autophagy and apoptosis in NMR skin fibroblasts. Serum starvation, H2O2 treatment, and LY294002 treatment all increased the LC3-II/LC3-I ratio and numbers of double-membraned autophagosomes and autophagic vacuoles, and decreased levels of p70S6K, p-Akt(Ser473), and p-Akt(Thr308). By contrast, CQ treatment decreased p70S6K, Akt(Ser473), and Akt(Thr308) levels. The Bax/Bcl-2 ratio increased after 12 h of exposure to LY294002 or CQ. These data show that inhibiting the Akt pathway promotes autophagy and apoptosis in NMR skin fibroblasts. Furthermore, LY294002 or CQ treatment decreased caspase-3, p53, and HIF1-α levels, suggesting that serum starvation or H2O2 treatment increase autophagy and apoptosis in NMR skin fibroblasts by inhibiting the PI3K/Akt pathway. CQ-induced inhibition of late autophagy stages also prevented Akt activation and induced apoptosis. Finally, the HIF-1α and p53 pathways were involved in serum starvation- or H2O2-induced autophagy in NMR skin fibroblasts.